Building a Highly Stable Ultrathin Nanoporous Layer Assisted by Glucose for Desalination. (September 2022) - Zhang, Yanqiu; Yang, Fan; Sun, Hongguang; Bai, Yongping; Li, Songwei; Shao, Lu
Abstract: Although nanoporous membranes are of great interest in desalination, it is still challenging to construct highly permeable nanoporous membranes with excellent rejections for an efficient desalination process. In this work, highly permeable nanoporous membranes were built from renewable resources, assisted by the versatile functions of glucose and dopamine, with coupling reactive groups via interfacial reaction with 1, 3, 5-benzenetricarbonyl trichloride (TMC). The small molecules (0.66 nm) of glucose, which have high hydrophilicity, can diffuse into the membrane for an effective reaction to ensure structural integration. Our novel ultrathin (∼44 nm) nanofiltration (NF) membrane exhibits ultra-high Na2 SO4 flux and excellent rejection of Na2 SO4 (66.5 L∙m −2 ∙h −1, 97.3%) and MgSO4 (63.0 L∙m −2 ∙h −1, 92.1%) under a pressure of 5 bar (1 bar = 10 5 Pa) which is much superior to the performance of natural-product NF membranes. The membrane demonstrates excellent long-term stability, as well as tremendous acid-base and alkali-base stability and high anti-pollution capacity. The designed membrane materials and architecture open a new door to biopolymer-based separation membranes beyond existing membrane materials.